2007
DOI: 10.1177/1046878106298271
|View full text |Cite
|
Sign up to set email alerts
|

Language simulations: The blending space for writing and critical thinking

Abstract: This article describes a language simulation involving six distinct phases: an in-class quick response, a card game, individual research, a classroom debate, a debriefing session, and an argumentative essay. An analysis of student artifacts—quick-response writings and final essays, respectively, both addressing the definition of liberty in a liberty-granting society—indicates a considerable betterment of the quality of the evidence supporting the writer's stance and/or the clarity of expression of that stance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
1
10
0
1
Order By: Relevance
“…These results confirmed that instructors recognized the benefits of simulations as originally articulated for the CIMARRON VALLEY simulation as well as results obtained by others: strategic competence (Salies, 2002a), collaboration (Halleck et al, 2002), interactive learning environments (Klabbers, 2001), rhetorical skills (Fukushima, 2007;Naidu, 2007), and critical thinking and argument (Kovalik & Kovalik, 2007). These results indicate that knowledge of many of the goals and underpinnings of simulations remained intact over time in the program.…”
Section: Promisessupporting
confidence: 89%
“…These results confirmed that instructors recognized the benefits of simulations as originally articulated for the CIMARRON VALLEY simulation as well as results obtained by others: strategic competence (Salies, 2002a), collaboration (Halleck et al, 2002), interactive learning environments (Klabbers, 2001), rhetorical skills (Fukushima, 2007;Naidu, 2007), and critical thinking and argument (Kovalik & Kovalik, 2007). These results indicate that knowledge of many of the goals and underpinnings of simulations remained intact over time in the program.…”
Section: Promisessupporting
confidence: 89%
“…The development of critical thinking skills is high on the agenda for HE establishments (Stassen et al, 2011;Roth 2010: Kovalik andKovalik, 2007;Halpern, 1998), and educators' teaching methods need to be adapted carefully to build on the students' current critical thinking skills in order to develop them The impact of critical thinking disposition on learning using business simulations. The International Journal of Management Education, 13(2), 119-12 http://dx.doi.…”
Section: Business Simulations In Higher Educationmentioning
confidence: 99%
“…It should be noted here that the card game via which we gathered our data was but a stage of a more encompassing classroom simulation; for more details relative to that simulation, see Kovalik and Kovalik (2007).…”
Section: Methodsmentioning
confidence: 99%